Lack of association between lysyl oxidase-like 1 polymorphism in pseudoexfoliation syndrome and pseudoexfoliation glaucoma in North Indian population. Issue 4 (July 2019) - Pandav, Surinder Singh; Chakma, Partha; Khera, Alka; Chugh, Neera; Gupta, Parul Chawla; Thattaruthody, Faisal; Seth, Natasha Gautam; Raj, Srishti; Kaushik, Sushmita; Khullar, Madhu; Ram, Jagat
Introduction: Pseudoexfoliation syndrome is commonly associated with pseudoexfoliation glaucoma. The two nonsynonymous single-nucleotide polymorphisms rs1048661 (R141L) and rs3825942 (G153D) within exon 1 of LOXL1 gene have been found to confer risk of pseudoexfoliation syndrome and pseudoexfoliation glaucoma in different geographical populations. This study aims to find association between two nonsynonymous single-nucleotide polymorphisms with pseudoexfoliation syndrome and pseudoexfoliation glaucoma in North Indian population. Methods: North Indian subjects clinically diagnosed with pseudoexfoliation syndrome/pseudoexfoliation glaucoma and normal age-matched control were enrolled in the study. Genomic DNA was extracted and the two single-nucleotide polymorphisms of LOXL1 gene were genotyped by polymerase chain reaction and sequencing. The association between single-nucleotide polymorphisms with pseudoexfoliation syndrome/pseudoexfoliation glaucoma was evaluated by chi-square test. Results: A total of 30 pseudoexfoliation glaucoma, 27 pseudoexfoliation syndrome and 61 control subjects were enrolled in the study. Patients with pseudoexfoliation syndrome and pseudoexfoliation glaucoma did not show any genetic association with either single-nucleotide polymorphism rs1048661 or rs3825942. Conclusion: The study shows lack of association between LOXL1 single-nucleotide polymorphisms and pseudoexfoliation in North Indian population.